2022
DOI: 10.31729/jnma.7858
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation among Patients Admitted to the Department of Internal Medicine in a Tertiary Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Atrial fibrillation is one of the commonest arrhythmias with an overall prevalence estimated to be 0.4-1% in the general population. The objective of this study was to find out the prevalence of atrial fibrillation among patients admitted to the Department of Internal Medicine in a tertiary care centre. Methods: A descriptive cross-sectional study was conducted among patients admitted to the Department of Internal Medicine of a tertiary care centre from 01 March 2021 to 01 March 2022. Ethical app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…[9][10][11][12] Our study shows male preponderance of 60.75% as compared to other various study done in our country which showed female preponderance as the studies have included both valvular and nonvolvular AF and as in our country as Rheumatic heart disease involving mitral valve is the most common cause of valvular AF and the common in female patients. [13][14][15][16][17] The mean CHA 2 DS 2 -VaSc and HAS-BLED score were 2.44±1.2 and 1.51±1.4 , respectively showing higher risk of stroke in the study population which were which were similar to other various study Kerala AF registry , Multicenter study in Thailand ,report from the euro heart survey on AF. 10,12,18 The type of atrial fibrillation in ours study as in order with 37.99% had permanent AF followed by 25.31% had paroxysmal AF, 16.45 % had persistent AF, Long standing persistent in 11.39% and first episode in 8.86 % similar to the various other study where permanent AF followed by paroxysmal AF and persistent AF accounts for majority of the type of AF.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[9][10][11][12] Our study shows male preponderance of 60.75% as compared to other various study done in our country which showed female preponderance as the studies have included both valvular and nonvolvular AF and as in our country as Rheumatic heart disease involving mitral valve is the most common cause of valvular AF and the common in female patients. [13][14][15][16][17] The mean CHA 2 DS 2 -VaSc and HAS-BLED score were 2.44±1.2 and 1.51±1.4 , respectively showing higher risk of stroke in the study population which were which were similar to other various study Kerala AF registry , Multicenter study in Thailand ,report from the euro heart survey on AF. 10,12,18 The type of atrial fibrillation in ours study as in order with 37.99% had permanent AF followed by 25.31% had paroxysmal AF, 16.45 % had persistent AF, Long standing persistent in 11.39% and first episode in 8.86 % similar to the various other study where permanent AF followed by paroxysmal AF and persistent AF accounts for majority of the type of AF.…”
Section: Discussionsupporting
confidence: 86%
“…only with warfarin ) varied from 9.6 % to 25.3 %. 7,8,16,17 The reason behind the increasing use of oral anticoagulant with NOACS is that with the increase availability of Novel anticoagulants such as rivaroxaban and dabigatran as national level pharmaceutical company produces it in recent years and as this study was done in tertiary cardiac center patients whom were mostly managed by cardiologist with adoption of the current recommended guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation